An Electrothermal Model to Predict Thermal Characteristics of Lithium-Ion Battery under Overcharge Condition - Charles Mohamed Hamisi; Pius Victor Chombo; Yossapong Laoonual; Somchai Wongwises (Energies, 2022)
Understanding the thermal characteristics of lithium-ion batteries (LIBs) under various operating situations is critical for improving battery safety. Although the application of LIBs in the real world is mostly transient, many previous models consider the phenomenon of the constant state. This study examines thermal behavior by developing a 2D electrothermal model to predict the thermal behavior of LIBs with overcharge abuse in high thermal conditions. The 18,650 cylindrical LiCoO2 graphite is investigated in a thermally controlled chamber at 35, 50, and 60 °C with a K-type thermocouple mounted on the LIB surface under charging rates of 1C, 2C, and 3C to acquire quantitative data regarding the thermal response of LIBs. Maximum critical temperatures are found at 62.6 to 78.9 °C, 66.4 to 83.5 °C, and 72.1 to 86.6 °C at 1C, 2C, and 3C, respectively. Comparing simulation analysis and experimental conditions, the highest relative error of 1.71% was obtained. It was found that relative errors increase as the charging rate increases. Moreover, increasing the charging current and surrounding temperature significantly increases the battery’s surface temperature. Furthermore, battery heat distribution appears almost uniform and tends to increase towards the positive terminal because cathode material is highly resistant. In addition, increasing the LIB heat transfer coefficient could positively improve the battery performance by eventually curbing the rise in battery temperature and reducing non-uniformity.